APPLICATION OF DATA ASSIMILATION METHOD FOR WAVE HEIGHT IN EASTERN VIETNAM SEA BY THE ENSEMBLE KALMAN FILTER - Thanh, Nguyen Trung; Huan, Nguyen Minh; Tien, Tran Quang (Vietnam Journal of Marine Science and Technology, 2019)
Advances in ocean data assimilation have been improved with the power of computers over the past 30 years, but the theory of data assimilation has a long history with the probability, theory of mathematical simulation, and traditional numerical calculations. Therefore, the research and application of data assimilation technology in oceanography have been widely carried out in the world and have gotten considerable achievements. In Vietnam, the study of data assimilation has also been applied in the meteorology and has attracted the increasing interest in oceanography. This paper presents the results of the study to calculate the wave height data from satellites combined with measured wave height data at MSP1 station of Vietsovpetro using the Ensemble Kalman Filter (EnKF) method associated with SWAN wave model in the Eastern Vietnam Sea